A Systematic Review of the Role Played by Aquaporins in the Etiology of Rheumatoid Arthritis - Modak, Debabrata; Kar, Shreya; Singh, Purnima; Roy, Sudipta Kumar; Bhattacharjee, Soumen (Asian Journal of Biological and Life Sciences)
Background: Aquaporins (AQPs) are integral membrane proteins that are essential for preserving the equilibrium of water. These proteins also regulate cell volume and cell migration as well as apoptosis that relates to various inflammatory diseases like Rheumatoid Arthritis (RA). Materials and Methods: From Scopus and Web of Science databases, recent report depicting the role of AQPs on RA pathophysiology between 2018-2023 were used to search related articles using specific keywords and parentheses to understand the current scenario of AQPs during RA pathogenesis as per PRISMA guidelines. Results: A total of 83 articles were retrieved initially, and after using automation tools, the number of reports came down to 20. Finally, 5 articles were retrieved from which data was extracted for summarising this finding. Conclusion: The study reports that AQPs are up-regulated in the synovium and cartilage of people with RA, and that AQP1 may be responsible for joint-swelling and synovial inflammation.
Keywords: Aquaporins; Inflammation; Rheumatoid arthritis; Synovial fibroblasts